2015
DOI: 10.1101/035220
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Initiator tRNA Genes Template the 3’CCA End at High Frequencies in Bacteria

Abstract: While the CCA sequence at the mature 3′ end of tRNAs is conserved and critical for translational function, a genetic template for this sequence is not always contained in tRNA genes. In eukaryotes and archaea, the CCA ends of tRNAs are synthesized post-transcriptionally by CCA-adding enzymes. In bacteria, tRNA genes template CCA sporadically. In order to understand variation in how prokaryotic tRNA genes template CCA, we re-annotated tRNA genes in the tRNAdb-CE database. Among 132,129 prokaryotic tRNA genes, i… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…It has been reported that in bacteria, CCA tails were sometimes included in tRNA gene templates. It has been reported that the templated 3'CCA sequence in bacteria was very common in the initial tRNA (tRNA fMet ), and it was also common in tRNA Tyr [58]. Coincidentally, in our gymnosperm plant chloroplast tRNA gene, tRNA fMet and tRNA Tyr of each species all carried the encoded 3'CCA sequence.…”
Section: Distribution Of Anti-codonmentioning
confidence: 47%
“…It has been reported that in bacteria, CCA tails were sometimes included in tRNA gene templates. It has been reported that the templated 3'CCA sequence in bacteria was very common in the initial tRNA (tRNA fMet ), and it was also common in tRNA Tyr [58]. Coincidentally, in our gymnosperm plant chloroplast tRNA gene, tRNA fMet and tRNA Tyr of each species all carried the encoded 3'CCA sequence.…”
Section: Distribution Of Anti-codonmentioning
confidence: 47%
“…We annotated the functional types of tRNA genes either as elongator isotypes by anticodon alone or, for those containing the CAU anticodon, into initiator tRNA Met (”X”), elongator tRNA Met , or tRNA Ile CA U (”J”) using TFAM v1.4 [4] with the TFAM model used in [3, 5]. We aligned tRNA sequences using COVEA v2.4.4 [19] and the prokaryotic tRNA covariance model from tRNAscan-SE [34].…”
Section: Methodsmentioning
confidence: 99%
“…21 For mycobacteria, the 3'-CCA of each tRNA is variably genomically encoded or added post-transcriptionally. 22 The resulting non-redundant reference library is then used to align forward and reverse sequencing reads, first separating uniquely aligned reads from reads matching multiple sequences in the library. Even with careful library curation, high sequence similarity or insufficient read length can result in multiply-mapped reads.…”
Section: Aqrna-seq Data Processing Workflowmentioning
confidence: 99%